2019
DOI: 10.3390/cells8020162
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Structures of the Dictyostelium Lamin NE81

Abstract: Nuclear lamins are nucleus-specific intermediate filaments (IF) found at the inner nuclear membrane (INM) of the nuclear envelope (NE). Together with nuclear envelope transmembrane proteins, they form the nuclear lamina and are crucial for gene regulation and mechanical robustness of the nucleus and the whole cell. Recently, we characterized Dictyostelium NE81 as an evolutionarily conserved lamin-like protein, both on the sequence and functional level. Here, we show on the structural level that the Dictyosteli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 62 publications
(101 reference statements)
1
19
0
Order By: Relevance
“…Both light and electron microscopy revealed reticular assemblies resembling those published for lamins in MEFs (Grafe et al, 2019;Shimi et al, 2015). Deconvolved ExM images revealed a close alignment of individual filaments in parallel arrangements of two to four filaments ( Fig.…”
Section: The Amoebozoan Laminsupporting
confidence: 58%
See 3 more Smart Citations
“…Both light and electron microscopy revealed reticular assemblies resembling those published for lamins in MEFs (Grafe et al, 2019;Shimi et al, 2015). Deconvolved ExM images revealed a close alignment of individual filaments in parallel arrangements of two to four filaments ( Fig.…”
Section: The Amoebozoan Laminsupporting
confidence: 58%
“…As in metazoan lamins, an α-helical, central rod domain consisting of 370 amino acid residues is preceded by a head domain including Dictyostelium nuclear envelope 511 a CDK1 phosphorylation consensus sequence and followed by (in this order) a tail domain featuring a NLS, a conserved lamin tail domain, and a CaaX-box (= cysteine, two aliphatic aa and X = residue specifying the type of isoprene moiety) for prenylation at the C-terminal end (Krüger et al, 2012). Furthermore, microscopic and molecular studies confirmed that NE81 should be considered as a bona fide lamin due to its localization, functions, and protein interactions Batsios et al, 2016a;Batsios et al, 2016b;Grafe et al, 2019;Krüger et al, 2012). For example, immunogold-electron microscopy revealed an exclusive distribution of NE81 along the inner nuclear envelope.…”
Section: The Amoebozoan Laminmentioning
confidence: 94%
See 2 more Smart Citations
“…We were the first to discover a bona fide lamin in a non-metazoan organism [7]. In a series of experiments including mutational analyses and in vitro assembly studies, we could show that the Dictyostelium lamin NE81 is not only evolutionarily related to metazoan lamins and capable of forming filaments of approximately 10 nm in diameter, but also fulfills typical lamin functions [7][8][9][10]. Not surprisingly, NE81 behaved more as a B-type lamin [11].…”
Section: Introductionmentioning
confidence: 98%